History of Gleason Works spiral bevel gear technology - Várkuli, Miklós Gábor; Bognár, Gabriella (Design of Machines and Structures, 2024)
The paper deals with the history of Gleason Works history in regard for their bevel gear manufacturing technology. In spiral bevel gear technology Gleason is a leading company, with many patterns and research studies in this field. The focus of this paper is to show the development of the technology provided by Gleason over the past more than 100 years.